Kajian Hukum tentang Itikad Tidak Baik dan Passing Off dalam Pelanggaran Merek Terkenal: Perspektif Putusan Mahkamah Agung Nomor 345 K/Pdt.Sus-Hki/2021 - Vera Yulia; Saidin Saidin; Tengku Keizerina Devi Azwar (Mahesa Research Center, 2024)
This article on legal studies aims to analyze the concept of bad faith and the passing off doctrine in the context of infringement of well-known brands, with a focus on the Supreme Court decision Number 345 K/Pdt.Sus-Hki/2021. This research uses a normative juridical approach through literature study and analysis of court decisions. This decision is interesting because it explains in depth how the court assesses the element of bad faith and the application of the passing-off doctrine in trademark disputes. The results of the study show that the Supreme Court applies international and national principles regarding the protection of well-known brands, and considers evidence of intent to imitate or mislead consumers. This research provides insight into the development of jurisprudence in Indonesia regarding legal protection of well-known brands and offers recommendations for legal practitioners in handling similar cases in the future.